2007
DOI: 10.1097/01.ccm.0000249828.81705.65
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute kidney injury on weaning from mechanical ventilation in critically ill patients*

Abstract: This study shows that renal dysfunction has serious consequences in the duration of mechanical ventilation, weaning from mechanical ventilation, and mortality in critically ill cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(140 citation statements)
references
References 33 publications
6
125
1
8
Order By: Relevance
“…When considering the sample's characteristics regarding male gender predominance, age and clinical diagnosis in the ICU hospitalization, pulmonary and cardiovascular diseases, the data was similar to that in the literature (9,(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…When considering the sample's characteristics regarding male gender predominance, age and clinical diagnosis in the ICU hospitalization, pulmonary and cardiovascular diseases, the data was similar to that in the literature (9,(15)(16)(17) .…”
Section: Discussionsupporting
confidence: 67%
“…The studies show an association of a determined co-morbidity that may or may not affect the appearance of ARF in ICU (8,11,17) . In this study, the restrictive factor located was the small number of comorbidities that, when grouped, did not allow to identify them as a risk factor to ARF.…”
Section: Discussionmentioning
confidence: 99%
“…Other uremic manifestations may have several explanations (encephalopathy, acidosis) or may be occult causes of other complications (bleeding diathesis and gastrointestinal bleed, leukocyte dysfunction with immunosuppression and nosocomial infection). In addition to the emerging data that appear to confirm an independent role of AKI in increasing mortality in the ICU, it is also clinically obvious that AKI is a cause of significant morbidity and severely complicates ICU management (57).…”
Section: Pulmonary Effects Of Akimentioning
confidence: 99%
“…a smaller study, Vieira et al 8 found a link between acute kidney injury and unsuccessful weaning from mechanical ventilation resulting in increases in duration of mechanical ventilation, lengths of stay, and ICU mortality.…”
Section: Prime Pointsmentioning
confidence: 99%